An Efficient Dynamic Mesh Generation Method for Complex Multi-Block Structured Grid (Advances in Applied Mathematics and Mechanics, 2014)
Aiming at a complex multi-block structured grid, an efficient dynamic meshgeneration method is presented in this paper, which is based on radial basis functions(RBFs) and transfinite interpolation (TFI). When the object is moving, the multi-blockstructured grid would be changed. The fast mesh deformation is critical for numericalsimulation. In this work, the dynamic mesh deformation is completed in two steps. Atfirst, we select all block vertexes with known deformation as center points, and applyRBFs interpolation to get the grid deformation on block edges. Then, an arc-lengthbased TFI is employed to efficiently calculate the grid deformation on block faces andinside each block. The present approach can be well applied to both two-dimensional(2D) and three-dimensional (3D) problems. Numerical results show that the dynamicmeshes for all test cases can be generated in an accurate and efficient manner.